Isolation of nonsense suppressor mutants in Pseudomonas. - Mindich, L (1976)
A strain of Escherichia coli harboring the drug resistance plasmid RP1 was treated with the mutagen N-methyl-N-nitro-N-nitro-N-nitrosoguanidine, and mutants were isolated in which ampicillin resistance had been lost due to an amber mutation in the plasmid. One of these mutants was again treated, and a strain was isolated in which tetracycline resistance was also lost due to an amber mutation in the plasmid. The plasmid containing amber mutations in the genes amp and tet was named pLM2. This plasmid could be transferred to strains of Pseudomonas aeruginosa, P. phaseolicola, and P. pseudoalcaligenes. Mutants resistant to ampicillin and tetracycline could not be obtained from P. phaseolicola carrying pLM2. However, strains of E. coli, P. aeruginosa, and P. pseudoalcaligenes carrying the plasmid did produce mutants simultaneously resistant to both antibiotics. All of the mutants of E. coli had developed nonsense suppressors since they became phenotypically lac+, although harboring a lac amber mutation, and formed plaques with amber mutants of phages PRR1 and PRD1 that attack organisms carrying RP1. Approximately 20% of the resistant mutants of P. aeruginosa and P. pseudoalcaligenes were sensitive to the amber mutant of PRD1. These mutants were of variable stability and grew somewhat more slowly than their parent strains. One of the suppressor mutants of P. pseudoalcaligenes, designated ERA(pLM2)S4, was used for the isolation of nonsense mutants of bacteriophage PHA6, a virus having a segmented genome of double-stranded ribonucleic acid and an envelope of lipids and proteins.